THE PORIFERA OF ALICANTE PROVINCE (SPAIN) - Martínez-Inglés, Ana Mª; Marín, A.; Ramírez-Díaz, L. (Anales de Biología, 1992)
A total of 36 species of Porifera have been found in some localities of the coast of Alicante, southeastem of Spain, from O to 50 m deep. Adreus fascicularis (Bowerbank, 1866) is new for the mediterranean coast, Samus anonyma Gray, 1867 for the Iberian Peninsula, and 24 of them for the Alicante province.